A simplified multivisceral transplantation procedure for patients with combined end‐stage liver disease and type 2 diabetes mellitus. Issue 9 (September 2017) - He, Xiao‐Shun; Fu, Shun‐Jun; Zhao, Qiang; Zhu, Xiao‐Feng; Wang, Dong‐Ping; Han, Ming; Ju, Wei‐Qiang; Ma, Yi; Jiao, Xing‐Yuan; Yuan, Xiao‐Peng; Hu, An‐Bin; Guo, Zhi‐Yong
Abstract : In liver transplant patients with type 2 diabetes mellitus (DM), the disease worsens after transplantation because of longterm use of diabetogenic immunosuppressive drugs, making management of those patients a great challenge. The objective of our study was to evaluate the safety and efficacy of a simplified multivisceral transplantation (SMT) procedure for the treatment of patients with end‐stage liver disease and concurrent type 2 DM. Forty‐four patients who had pretransplant type 2 DM were included. A total of 23 patients received SMT, and 21 patients received orthotopic liver transplantation (OLT). Patient and graft survivals, complications, diabetic control, and quality of life (QOL) were retrospectively analyzed in both groups. The 1‐, 3‐, and 5‐year cumulative patient and graft survival rates were 91.5%, 75.4%, and 75.4% in the SMT group and were 94.4%, 64.4%, and 64.4% in the OLT group, respectively ( P = 0.70). Interestingly, 95.7% (22/23) of patients achieved complete remission from DM after SMT compared with 16.7% (3/18) of patients after OLT. The occurrence of biliary complication was significantly higher in the OLT group than that in the SMT group (23.8% versus 0.0%; P = 0.01). Moreover, better QOL was observed in the SMT group than that in the OLT group. In conclusion, the SMT procedure we described here is a safe and viable option for patients with end‐stage live disease and concurrent type 2 DM. This SMT procedure offers excellent transplant outcomes and QOL. Liver Transplantation 23 1161–1170 2017 AASLD.